2010
DOI: 10.1208/s12249-010-9396-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug Release From Coated Pellets Based on Isomalt, Sugar, and Microcrystalline Cellulose Inert Cores

Abstract: Abstract. The objective of the present study was to investigate the effect of the pellet core materials isomalt, sugar, and microcrystalline cellulose on the in vitro drug release kinetics of coated sustainedrelease pellets as well as to evaluate the influence of different ratios of polymethacrylate copolymers exhibiting different permeability characteristics on the drug release rate. For characterization of the drug release process of pellets, the effect of osmolality was studied using glucose as an osmotical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Regarding the starter cores, no major differences were observed in terms of composition, except the lower release rate obtained from TAP beads which may be related to a stronger interaction between the SDM and the acidic groups in the core instead of the 4ASA. However, other authors have reported significant differences in drug release depending on the composition of the core material [45][46][47]. As expected, the particle size of the beads has a significant effect on the physicochemical characteristics of the cocrystal.…”
Section: Aureussupporting
confidence: 58%
“…Regarding the starter cores, no major differences were observed in terms of composition, except the lower release rate obtained from TAP beads which may be related to a stronger interaction between the SDM and the acidic groups in the core instead of the 4ASA. However, other authors have reported significant differences in drug release depending on the composition of the core material [45][46][47]. As expected, the particle size of the beads has a significant effect on the physicochemical characteristics of the cocrystal.…”
Section: Aureussupporting
confidence: 58%
“…Sustained drug release is generally needed in the case of drug‐loaded implants,1 tissue scaffolds (tissue engineering),2 and wound dressings3 to attain an adequate long‐term effect. However, in the case of oral dosage forms, enhanced dissolution is often required, in addition to sustained drug release,4–6 to achieve sufficient bioavailability 7. It is a significant challenge for pharmaceutical technologists because of the increasing number of drugs with poor water solubility 8,9…”
Section: Introductionmentioning
confidence: 99%
“…In controlled release diclofenac sodium pellets, based on isomalt, sugar, and microcrystalline cellulose, it was comparatively observed that dissolution rates for the soluble sucrose-and isomalt-based pellets were similar and were significantly higher compared to those of the microcrystalline cellulose-based pellets [24]. Table 2 summarizes the calculated regression parameters for the release profile of metronidazole tablets containing a fixed proportion of Noveon AA1 (20%) and different proportions of GalenIQ 720.…”
Section: Experimental Points and Calculated Regressionsmentioning
confidence: 99%